PENGARUH MANAJEMEN TALENTA DAN MANAJEMEN PENGETAHUAN DALAM PENINGKATAN KINERJA PEGAWAI PT. BANK BNI (PERSERO) Tbk. KANTOR CABANG UTAMA KOTA MAKASSAR - Sri Fausiah Rahmayanti; Fitriani Latief; Nurkhalik Wahdanial Asbara; Iradat Rayhan Sofyan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat ITB Nobel Indonesia, 2024)
This study aims to analyze (1) The partial influence of talent management and knowledge management on employee performance. (2) The simultaneous influence of talent management and knowledge management on employee performance. (3) The most dominant variable affecting employee performance at PT Bank BNI (Persero) Tbk. Main Branch Office in Makassar City. This study uses a quantitative method. The research sample consists of 30 respondents who are permanent employees of PT Bank BNI (Persero) Tbk. Main Branch Office in Makassar City. This research uses multiple linear regression analysis method with data collection using a questionnaire with a Likert scale. The results of this stud show that (1) The variables of talent management and knowledge management partially have a positive and significant effect on employee performance. (2) The variables of talent management and knowledge management simultaneously have a positive and significant effect on employee performance. (3) The variable of Knowledge Management is the most dominant variable affecting Employee Performance at PT Bank BNI (Persero) Tbk. Main Branch Office in Makassar City.